Call for Caution to Consider Babesia bovis and Babesia bigemina as Anthropozoonotic Agents in Colombia. Comment on Kumar et al. The Global Emergence of Human Babesiosis. Pathogens 2021, 10, 1447 - Carlos Ramiro Silva-Ramos; Álvaro A. Faccini-Martínez (Pathogens, 2022)
Currently, six species and two genetic variants within Babesia genus have been confirmed as human pathogens. Babesia bovis and Babesia bigemina are causative agents of bovine babesiosis, and, in spite of the worldwide distribution of those species and their vectors, no description of related human cases has been reported. As a contribution, we would like to address the articles which claim the alleged role of B. bovis and B. bigemina as anthropozoonotic pathogens in Colombia.